Feminisme Indonesia - Wibowo, Bayu Ananto (KARMAWIBANGGA Historical Studies Journal, 2022)
This study uses the method of a literature review. The purpose of this research is to produce studies that are useful for understanding certain phenomena or deepening our understanding of Indonesian feminism. The result of this research is an understanding of the study of Indonesian feminism, which includes many themes and issues related to women's rights, gender equality, and violence against women. As a social and political movement, feminism in Indonesia has experienced developments and changes since its inception in the 1900s. However, feminism in Indonesia is also faced with many challenges, such as cultural and social resistance to the concept of gender equality, the use of religion and traditions as tools to justify discrimination against women, and a lack of awareness and understanding of feminist issues among the public. Overall, the study of Indonesian feminism is an important movement in advocating for women's rights and gender equality.